2015
DOI: 10.1007/s00787-015-0710-8
|View full text |Cite
|
Sign up to set email alerts
|

Identifying children and adolescents at ultra high risk of psychosis in Italian neuropsychiatry services: a feasibility study

Abstract: The past 20 years have seen the evolution of the construct of a clinical high-risk (hereafter, HR) state for psychosis. This construct is designed to capture the pre-psychotic phase. Some aspects of this approach, such as its feasibility in children and adolescents, are still under investigation. In the present study, we address the feasibility of implementing prodrome clinics for HR individuals within the framework of Italy's national child and adolescent neuropsychiatry services and the clinical relevance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 62 publications
3
34
1
1
Order By: Relevance
“…Only 3.3% of our sample met ANS criteria exclusively, although 76.9% of the sample reported ANS combined with other criteria, in line with other published results (Spada et al, ). The idea of including patients with ANS without APS symptoms was inspired by the Recognition and Prevention Program in New York (Cornblatt, ; Lencz et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Only 3.3% of our sample met ANS criteria exclusively, although 76.9% of the sample reported ANS combined with other criteria, in line with other published results (Spada et al, ). The idea of including patients with ANS without APS symptoms was inspired by the Recognition and Prevention Program in New York (Cornblatt, ; Lencz et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, most PRSS reported APS at baseline, a larger proportion also presented ANS, while few showed GR plus deterioration, in line with results from other child and adolescent PRS studies (Cascio et al, 2016;Meyer et al, 2005;Spada et al, 2016;Ziermans et al, 2011).…”
Section: Prs Sample Baseline Clinical Characteristicssupporting
confidence: 92%
See 1 more Smart Citation
“…Australia (Conrad et al, 2017;Yung et al, 2006Yung et al, , 2008; 3 others emphasized an Asian perspective (Katsura et al, 2014;M. M. L. Lam et al, 2006;Lee et al, 2013) and another a Canadian point of view (Pruessner et al, 2015); 2 focused particularly on paediatric and youth (<18 years) populations (Spada et al, 2016;Welsh & Tiffin, 2014). Two studies analysed recruitment strategies in the framework of early detection (Francesconi et al, 2016;Rietdijk et al, 2012).…”
Section: Participating Departmentsmentioning
confidence: 99%
“…Broome et al, 2005;Demjaha et al, 2012;Fusar-Poli et al, 2013Hui et al, 2013;Ising, Kraan, et al, 2016;Ising, Ruhrmann, et al, 2016;Klauser et al, 2015;T. C. Kraan et al, 2017;Landa et al, 2016;Lee et al, 2013;Lim et al, 2015;Morcillo et al, 2015;Morrison et al, 2011;Rietdijk et al, 2010Rietdijk et al, , 2013Rutigliano et al, 2016;Spada et al, 2016;Valmaggia et al, 2014;Velthorst et al, 2012;Winton-Brown et al, 2015) (see Table 1). Only Table 1).…”
Section: Ethnicityunclassified